An Application of Forecasting Technique for Production Planning: A Case Study of UK ENGINEERING & SUPPLY Co.,Ltd. - อ่ำดี, นพดล; พันธ์บุญมี, วราวุธ (Journal of Roi Et Rajabhat University, 2016)
This research aims to forecast data of time series derived from the classical models. The raw data was production volume of automotive parts from UK ENGINEERING & SUPPLY Co., Ltd., produced within 68 months from January, 2010– August,2015. The forecasting models of were employed for the classical with multiplicative model and equation was equal to 62.12-0.764t+0.01676t2. The mean square error (MSE) was 31,167 pieces or 358 pieces/month and mean absolute percentage error (MAPE) was 25.67% or 0.41 percent/month.